Comparative Study on Galling and Antiwear Behavior of Polyurethane Based Coatings Reinforced With Pristine and Alkylated MoS2 Nanosheets - Kashyap A.; Harsha A.P.; Rawat S.S.; Barshilia H.C. (My University, 2025)
The present investigation is focused on tribological studies of polyurethane (PU) based coatings doped with nano-MoS2, and MoS2 functionalized with octadecanethiol (i.e., MoS2-ODT) on steel substrate. The PU-based nanocomposite coatings showed enhanced hardness, scratch and galling resistance at room temperature. Tribological tests were carried out under two contact conditions, i.e., sliding contact for galling resistance and reciprocating wear studies. The PU-based nanocomposite coatings showed enhanced galling resistance at room temperature. The reciprocating wear studies showed a significant reduction in friction and wear with the addition of MoS2 and MoS2-ODT nanosheets in the polymer matrix. The PU-MoS2 coating showed a 46% and 77% reduction in coefficient of friction and wear, respectively. However, the PU-MoS2-ODT nanocomposite coatings showed up to 75% and 95% reduction in coefficient of friction and wear, respectively. The PU based nanocomposite coating also showed enhanced galling resistance up to 17.5 MPa, in contrast to 5 MPa of SS 304. Different tools like high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), Fourier transform infrared radioscopy (FTIR), high resolution scanning electron microscopy (HRSEM), energy dispersive X-ray (EDS), nanoindentation, stereo-zoom, and optical microscopies were used for the characterization and study of MoS2 nanosheets and PU based nanocomposite coatings. Copyright © 2022 by ASME.